Environmental forensics for persistent organic pollutants (Elsevier, 2014)
Environmental Forensics for Persistent Organic Pollutants represents the state-of-the-art in environmental forensics in relation to persistent organic pollutants (POPs). The book is a complete reference for practitioners and students, covering a range of topics from new analytical techniques to regulatory and legal status in the global community. Through case studies from leading international experts, real-world issues - including the allocation of responsibility for release into the environment - are resolved through the application of advanced analytical and scientific techniques. This book introduces and assesses the development of new techniques and technologies to trace the source and fate of newly emerging and classic POPs (perfluoroalkyl substances, brominated flame retardants, organochlorine pesticides, perfluorinated chemicals, polycyclic aromatic hydrocarbons, and polychlorinated biphenyls) in environmental media, including atmospheric, marine, freshwater, and urban environments. Real-world case studies show the application of advanced analytical and scientific techniquesDiscussion of GC-GC provides an introduction and assessment of a novel technique from leaders in the fieldIntroduces the development of new analytical techniques (such as 2-D GCHC and LC-LC) to trace the source and fate. Raises awareness about the health and environmental impact of persistent organic pollutants (POPs)Outlines the development of international measures to control POPs so that chemists can understand the legal issues.